Recurrent Gastrointestinal Bleeding in a Man with Osler-Weber-Rendu Syndrome and Intestinal Varices - Robert N. Clark; William G. Paterson; Laurington R. DaCosta; Ivan T. Beck (Canadian Journal of Gastroenterology)
A patient with Osler-Weber-Rendu disease and idiopathic intestinal varices who presented with recurrent gastrointestinal hemorrhage and iron deficiency anemia is reported. The unique coexistence of these two rare disorders is discussed and the literature reviewed.